Die oudste boodskap via die nuutste massamedium: evaluering van ‘n e-pos dagstukkiediens - Lombaard, Christo (Verbum et ecclesia, 2005)
This study focuses on daily devotionals from the Old Testament that are sent to subscribers by means of email. A questionnaire was circulated among subscribers to this free service, to ascertain their experience of these devotionals. High levels of satisfaction and a positive orientation were found with regards to both the content and the medium of dissemination. Recommendations for the further expansion of this electronic service are offered.